Pengaruh Pendidikan, Umur, Jenis Kelamin, Lama Usaha, Modal Dan Pendapatan Terhadap Mobilitas Usaha Pedagang Kaki Lima Di Handil Bakti Kabupaten Barito Kuala - Rizki Agustina; Ahmad Yunani (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This research aims to know and analyze how much influence education, age, gender, lengthof business, capital, and income to Business street vendors' mobility in Handil Baktiregency of Barito Kuala. The method used in this research is the quantitative method, withthe education variable, age, gender, length of effort, capital and income to the mobilitybusiness of the street vendors in Handil Bakti regency of Barito Kuala, data usedCoeseoner primary and interviews with data 58 respondents and data analysis techniquesusing Binary logistic regression. The results of this study showed that the length of businesshas a partial influence on the mobility of company of the street vendors in Handil BaktiDistrict Barito Kuala; education, age, gender, capital, and income are simultaneouslyinfluential to The mobility of business of the street vendors in Handil Bakti of Barito KualaDistrict and variables that are the dominant influence on the mobility of company of thestreet vendors in Handil Bakti District Barito Kuala is the old business